TEACHER LEARNING WITHIN THE SCHOOL CONTEXT: AN ECOLOGICAL PERSPECTIVE - Canh, Le Van; Minh, Nguyen Thi Thuy (Universitas Pendidikan Indonesia, 2012)
Abstract: Central to teacher professional development is teacher learning, which is situated in a classroom, a school, or an informal social setting. Using an ecological framework which incorporates a wide range of influences at multiple levels, including intrapersonal, interpersonal/ cultural, institutional, and physical environment, this research sets out to explore the influence of the school context on teachers’ engagement in informal learning activities. Data are collected through semi-structured open-ended interviews with six EFL teachers working in different upper secondary schools in Vietnam in an attempt to uncover what types of informal learning activities these teachers engage in and how the school context affects their engagement. Findings show multiple work-based factors that influence teacher learning in the school. The study provides evidence to teacher educators about the relationship between school context and teachers’ degree of engagement in informal learning. Keywords: ecological framework, professional development, informal learning, personal characteristics, teacher learning